Radiative sky cooling potential maps of China based on atmospheric spectral emissivity. (April 2021) - Zhu, Yazhu; Qian, Hua; Yang, Ronggui; Zhao, Dongliang
Highlights : Radiative sky cooling potential maps of China have been calculated. For clear sky condition, ideal selective surface has annual radiative cooling power 60–85 W/m 2 . For all sky conditions, ideal selective surface has annual radiative cooling power 35–45 W/m 2 . The annual and summer radiative cooling powers across China decrease from northwest to southeast. Abstract: Radiative sky cooling has broad application prospects in different areas for energy-saving. Obtaining local cooling potential is critical for guiding the design of radiative cooling system. Most empirical models for estimating radiative cooling potential in specific regions are based on the concept of effective atmospheric emissivity. The use of atmospheric spectral emissivity to calculate atmospheric longwave downward radiation is limited. In this work, we propose a method that uses local meteorological data to generate the atmospheric spectral emissivity and calculate the radiative cooling potential under clear and all sky conditions. The calculated radiative cooling potential in China is based on hourly meteorological data from 271 observation stations. The spatial distribution maps of radiative cooling potential under different conditions are plotted. For ideal broadband and ideal selective surfaces, the annual average radiative cooling potential in most parts of China is 70–100 W/m 2 and 60–85 W/m 2 respectively under clear sky condition, and 40–55 W/m 2 and 35–45 W/m 2 respectively under all sky conditions. For clear sky condition, western China has a maximum annual average cooling potential of over 100 W/m 2, while southeastern China has an annual average cooling potential of around 50 W/m 2 . The monthly average radiative cooling potential in several major cities in different building climate demarcations is also discussed. Results obtained in this work can provide guidance for the design of radiative sky cooling system.